Solving A G-Co-Coercive General Variational Inequalities With A Modified Projection Method (Journal of Namibian Studies : History Politics Culture, 2023)
In this paper, we propose a descent direction method for solving general varitio inequalities. The new iterative method is obtained by using three-steps. We show that the method is globally convergence under that the operator is g-co-coercive wich is weaker than strong monotonicity and the  solution set is nonempty.